Application and Integration of VIAF and OCLC FAST with Koha, VuFind, and Google CSE. Issue 3 (2nd October 2022) - Saha, Sujan; Mandal, Sukumar
Abstract: The purpose of Digital Library system is collection of electronic objects. The "authorities" module runs the entire mechanism for fetching the authority data from the remote server. The study explores mechanisms for integration activities behind the authority control and practical evaluation. This study has been done on the publicly accessible online library OPAC through Google Form tools. It demonstrates that all authority control tools can manage several headings than just one or a few. The research seeks explanation through systematically searching observations of Online OPAC databases for studies of authority control. According to the findings, AuthorityBox is a Koha add-on that enhances the system's functionality. It complies with VIAF identifiers and other MARC21 authority data to compliance with RDA Cataloguing Guidelines. The open source integrated library system Koha enables easy authority import into the ILS-OPAC search engine. Statistically, Haringhata Mahavidyalaya, West Bengal, India used the most authority terms, with 24, 820 personal names and 53, 256 topical terms. This study reviews the many recommendations and techniques for designing a library discovery authority framework. It also focuses on the software and standards for integrating VIAF with Koha, VuFind, and Google Custom Search Engine for importing authority data from other libraries via the Z39.50 server.